Leveraging FinTech for positive ESG outcomes through regional innovation: insights from a knowledge capital perspective - Sun, Xinrui; Wu, Guo (Frontiers in Public Health, 2025)
Financial technology (FinTech) is an increasingly important driver of sustainable development, with a crucial role in influencing environmental, social, and governance (ESG) outcomes that underpin public health and well-being. In this study, we theoretically and empirically examine the impact of FinTech on regional ESG performance. Our empirical analysis is based on a panel dataset covering 31 Chinese provinces from 2011 to 2023. We provide evidence that FinTech enhances regional ESG performance, primarily by promoting regional innovation. Drawing on a tentative knowledge capital model, we show that the innovation-enhancing effect is achieved by improving innovation efficiency and reducing innovation costs related to sustainable practices. Furthermore, the positive impact of FinTech on regional ESG performance is more pronounced in regions with lower income disparity and higher urbanization. These findings highlight the need for differentiated FinTech policies, tailored to local socio-economic and environmental conditions, to effectively support ESG goals, foster regional sustainable development, and ultimately contribute to improved public health and well-being.